Primary malignant tumors of the heart: Outcomes of the surgical treatment. (July 2015) - Pacini, Davide; Careddu, Lucio; Pantaleo, Antonio; Parolari, Alessandro; Leone, Ornella; Daprati, Andrea; Gargiulo, Gaetano Domenico; Di Bartolomeo, Roberto
Background: Malignant cardiac tumors are rare and have an extremely poor prognosis even when complete resection is attempted. The aim of this study was to review the experience of primary malignant cardiac tumors in 2 Italian academic hospitals. Methods: The hospital records were searched to identify patients with primary malignant cardiac tumors who underwent surgery between January 1979 and December 2012. Secondary cardiac tumors, whether metastatic or invasive, were excluded as were primary sarcomas of the great arteries. Fourteen patients selected from our institution's surgical series were identified. Eleven (78.6%) were men and 3 (21.4%) were women, and the mean age at surgery was 47.4 years. Results: The most common histological type was angiosarcoma (28.6%). The mean survival was 28.8 ± 28 months and it was better in men than in women (30.5 ± 8.7 vs. 21.1 ± 3.2 months). Patients with a radical resection at the first surgery had a longer survival compared to patients with a partial resection (39.9 ± 23.2 vs. 24 ± 4 months). Conclusions: The treatment outcome for patients affected by primary malignant heart tumors remains poor. Aggressive surgery alone does not provide good results in terms of survival rate. A new multidisciplinary approach is mandatory to improve long-term survival.